Le Cervin, sommet mythique et géomorphosite emblématique des Alpes suisses - Francis Huguet (Physio-Géo)
Matterhorn, with its pyramidal shape, nearly obsessing in Switzerland, is since its conquest in 1865 an emblematic mountain in the history of mountaineering. But it is also the object of important geological and geomorphologic researches: place in the structure of Alpine range, carving by intersecting glacial cirques, issue of melting of high mountain permafrost. Bearing at the same time a scientific and emblematic value in Switzerland, it can be regarded as a well-characterized geomorphosite.